(untitled) (Pulse, 2025)
Background: Prader-Willi syndrome (PWS) is a heterogeneous genetic disorder caused by an anomaly on the chromosome 15. This condition typically results in low muscle tone, reduced height, cognitive impairments, and persistent feelings of hunger, which can lead to severe obesity. Additional common challenges associated with PWS include disturbances in thermoregulation, arrhythmia, diabetes mellitus, and seizures. These multisystemic issues create unique challenges in anesthetic management, making thorough perioperative planning essential to minimize potential complications. Case Presentation: We present the case of a 19-year-old male with PWS who underwent laparoscopic hernioplasty and cholecystectomy under general anesthesia. The perioperative course was largely uneventful, with successful weaning from mechanical ventilation. The only notable occurrence was transient, intermittent hypertension during pneumoperitoneum, which was effectively managed without complications. Conclusion: Careful perioperative planning and multidisciplinary management enable safe anesthesia and favorable surgical outcomes in patients with Prader–Willi syndrome. Pulse Vol.17, 2025 P: 23-28